Poly(glutamic acid) nanofibre modified glassy carbon electrode: Characterization by atomic force microscopy, voltammetry and electrochemical impedance - Santos, Daniela Pereira (2008)
Glassy carbon electrodes (GCE) were modified with poly(glutamic acid) acid films prepared using three different procedures: glutamic acid monomer electropolymerization (MONO), evaporation of poly(glutamic acid) (PAG) and evaporation of a mixture of poly(glutamic acid)/glutaraldehyde (PAG/GLU). All three films showed good adherence to the electrode surface. The performance of the modified GCE was investigated by cyclic voltammetry and differential pulse voltammetry, and the films were characterized by atomic force microscopy (AFM) and electrochemical impedance spectroscopy (EIS). The three poly(glutamic acid) modified GCEs were tested using the electrochemical oxidation of ascorbic acid and a decrease of the overpotential and the improvement of the oxidation peak current was observed. The PAG modified electrode surfaces gave the best results. AFM morphological images showed a polymeric network film formed by well-defined nanofibres that may undergo extensive swelling in solution, allowing an easier electron transfer and higher oxidation peaks.